2017
DOI: 10.26418/jebik.v6i2.22985
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pengeluaran Pemerintah Bidang Pendidikan, Gender Gap dan Pendapatan Per Kapita Terhadap Ketimpangan Pendidikan dan Ketimpangan Pendapatan Kabupaten/Kota di Provinsi Kalimantan Barat

Abstract: This study aims to analyze the impact of government expenditures, gender gap and per capita income on the education and income inequalities of regencies and cities in West Kalimantan Province. This research used secondary data in a form of data panel. These data include time series data for 5 years (2011 -2015) and cross-section data for 14 regencies and cities in West Kalimantan Province. The results showed that the government expenditures and per capita income have significant negative effect on the educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
2
2
1
5
Order By: Relevance
“…The education level of the 10-year-old of the population who have completed primary or not attending school and university graduates in 2016 in Pandeglang Regency is 73.2% and 4.56%, those in Lebak Regency were 72.21% and 3.12% respectively, while those in Tangerang Municipality was 30.18% and 13.63%, all of which indicating the unequal condition. These results confirm the previous research that per capita income raises appear to increase educational disparity over time (Lee & Lee 2018;Naveed et al 2018;Teng 2019), but do not correspond to research (Mesa 2007 andHamzah 2017) who found otherwise. There are several reasons for school-age children to complete school at higher levels, one of the reasons for economic reasons is to work and have an income (BPS 2014;Nurmaidah & Gautama 2020).…”
Section: Results Of Empirical Modelsupporting
confidence: 72%
See 1 more Smart Citation
“…The education level of the 10-year-old of the population who have completed primary or not attending school and university graduates in 2016 in Pandeglang Regency is 73.2% and 4.56%, those in Lebak Regency were 72.21% and 3.12% respectively, while those in Tangerang Municipality was 30.18% and 13.63%, all of which indicating the unequal condition. These results confirm the previous research that per capita income raises appear to increase educational disparity over time (Lee & Lee 2018;Naveed et al 2018;Teng 2019), but do not correspond to research (Mesa 2007 andHamzah 2017) who found otherwise. There are several reasons for school-age children to complete school at higher levels, one of the reasons for economic reasons is to work and have an income (BPS 2014;Nurmaidah & Gautama 2020).…”
Section: Results Of Empirical Modelsupporting
confidence: 72%
“…The finding of previous research concluded that there was a positive association between the degree of income inequality and education inequality (Abdelbaki 2012;Coady & Dizioli 2018). Hamzah et al (2017) and Mesa (2007) also concluded that GDRP per capita was negatively correlated to education inequality. The education level in the high-income district was likely higher than that of low-income district, the educational inequalities were more likely to be greater than those in high-income districts (Naveed et al 2018).…”
Section: Introductionmentioning
confidence: 89%
“…Ketimpangan pendidikan Jawa Timur justru tertinggi di Pulau Jawa dan di KBI. Capaian pendidikan yang timpang akan menyebabkan perbedaan kualitas sumber daya manusia yang implikasinya berupa perbedaan produktivitas di antara para pekerja sehingga berdampak pada ketimpangan pendapatan antarpekerja dan ketimpangan pembangunan (Sullivan & Smeeding, 1997;Ashenfelter & Rouse, 2000;Gregorio & Lee, 2002;Hamzah, 2017). Dengan demikian, perlu dikaji determinan ketimpangan capaian pendidikan kabupaten/kota di Jawa Timur dari waktu ke waktu.…”
Section: Jurnal Dinamika Ekonomi Pembangunanunclassified
“…Menurutnya, capaian rata-rata lama sekolah (RLS) yang semakin tinggi cenderung menurunkan ketimpangan pendidikan serta gender gap yang semakin tinggi dapat meningkatkan ketimpangan pendidikan. Kemudian Soejoto et al (2016) Hamzah et al (2017), pengeluaran pemerintah untuk pendidikan dan pendapatan perkapita signifikan menurunkan ketimpangan pendidikan.…”
Section: Jurnal Dinamika Ekonomi Pembangunanunclassified
See 1 more Smart Citation